An Investigation of the Relationship Between Psychological Strengths and the Perception of Bullying in Early Adolescents in Schools - Anderson, Chris G.; Rawana, Edward P.; Brownlee, Keith; Whitley, Jessica (Alberta Journal of Educational Research, 2011)
This study explored the association between psychological strengths and perceptions of being a victim of a bullying relationship in the school environment. Using self-report questionnaires with grades 7 and 8 students, the role of psychological strengths as potential protective factors against various forms of bullying were examined including the patterns of strengths associated with the bullying experience. The results showed no significant association between global indices of strengths and perceptions of victimization. However, significant relationships did emerge between specific strengths and victimization. Strengths in school functioning among boys but not girls and strengths in personality functioning for both sexes were associated with lower perceived victimization. In contrast, strengths in spiritual and cultural identification were associated with perceptions of increased victimization. The implications of these results for anti-bullying strategies are discussed. Cette étude a porté sur l'association entre les forces psychologiques et les perceptions d'être victime d'intimidation à l'école. En nous appuyant sur des questionnaires d'auto-évaluation auprès d'élèves en 7e et 8e année, nous avons examiné le rôle des forces psychologiques comme facteurs potentiels de protection contre diverses formes d'intimidation. L'étude a également porté sur les modèles de forces associés à l'expérience de l'intimidation. Les résultats n'ont indiqué aucune association entre les indices globaux de forces et les perceptions de l'intimidation. Toutefois, des relations significatives sont ressorties entre des forces spécifiques et l'intimidation. Des forces relatives à l'école chez les garçons mais pas les filles, et des forces relatives à la personnalité chez les garçons et les filles, étaient associées à une perception amoindrie de la victimisation. Par contre, des forces relatives à l'identification spirituelle et culturelle étaient associées à des perceptions accrues de victimisation. Nous discutons des répercussions de ces résultats sur les stratégies contre l'intimidation.